Single-molecule chemical reactions on DNA origami - Voigt, Niels Vinther; Tørring, Thomas; Rotaru, Alexandru; Jacobsen, Mikkel F.; Ravnsbæk, Jens B.; Subramani, Ramesh; Mamdouh, Wael; Kjems, Jørgen; Mokhir, Andriy; Besenbacher, Flemming; Gothelf, Kurt Vesterager (Nature nanotechnology, 2010)
DNA nanotechnology1,2 and particularly DNA origami3, in which long, single-stranded DNA molecules are folded into predetermined shapes, can be used to form complex self-assembled nanostructures4,5,6,7,8,9,10. Although DNA itself has limited chemical, optical or electronic functionality, DNA nanostructures can serve as templates for building materials with new functional properties. Relatively large nanocomponents such as nanoparticles and biomolecules can also be integrated into DNA nanostructures and imaged11,12,13. Here, we show that chemical reactions with single molecules can be performed and imaged at a local position on a DNA origami scaffold by atomic force microscopy. The high yields and chemoselectivities of successive cleavage and bond-forming reactions observed in these experiments demonstrate the feasibility of post-assembly chemical modification of DNA nanostructures and their potential use as locally addressable solid supports.
Gesehen am 12.09.2023